Unusual Cases in Peritoneal Surface Malignancies - Canbay, Emel (Springer International Publishing : Imprint: Springer, 2017)
This book has been designed to provide the full description of the comprehensive management of peritoneal surface malignancies which have originated from different primaries, such as breast cancer, small bowel cancers and imatinib resistant GISTosis and sarcomas and pseudomyxoma. The book provides the most up-to-date information on current approaches such as cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Given the increasing evidence that the patients who may benefit from this treatment modality avoid potential lethal course of these diseases, the book explores the application of these approaches to a number of types of malignancy. The first chapters explore Benign Multicystic Mesothelioma and Pseudomyxoma Peritonei arising from unusual primaries. Among other explored topics are peritoneal metastases from serous papillary uterine carcinoma, sarcoma and from unusual origins. This book is valuable for surgical oncologists who deal with the management of peritoneal surface malignancies.
Keywords: Medicine.; Oncology.; Surgery.; elektronické knihy; electronic books